Employee Personality in Improving Organizational Citizenship Behavior (OCB) with Its Impact on Employee Performance - R.S, Salsa Faradilla; Rosita, Sry; Chairunnisa, Fitri (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
This study aims to determine the influence of Employee Personality in increasing Organizational Citizenship Behavior (OCB) with its impact on Employee Performance at the Regional Research and Development Agency Office of Jambi Province. This type of research is Quantitative Research with a population of 56 people from all employees of the Balitbangda Office. This data was collected by distributing questionnaires. Data analysis techniques are descriptive analysis and SEM analysis. Based on calculations using SMARTPLS version 4.0, the results show that Employee Personality has a positive and significant influence on OCB. Employee Personality has a positive and significant influence on Employee Performance.